Land debt in the legislation and practice of the Republic of Slovenia - Vujović Dragana (Zbornik Radova Pravnog Fakulteta u Nišu)
In 2003, the Republic of Slovenia adopted a new Real Property Code. One of the most significant novelties brought about by that code was the expansion of the numerus clausus of real subjective rights by introducing the institute of land debt, as a non-accessory lien, following the example of the German and Swiss institutes. The function of land debt is basically the same as the function of mortgage, i.e. to secure the provision of a specific claim or debt, but its main advantage over a mortgage is its non-accessory nature. In contrast to Germany, since its introduction, land debt has been a less frequently used institute in business practice in Slovenia. In the last few years, before its abolition in 2013, land debt came to the attention of the Slovenian public as an instrument that was almost exclusively used by suspected and accused persons to secure property in order to avoid paying debts. In this paper, the author analyzes the normative framework of this new institute, as well as the reasons for its abolition and deletion from the legal system of the Republic of Slovenia after ten years of existence.